Discovery of molecular mechanisms of lignan justicidin A using L1000 gene expression profiles and the Library of Integrated Network-based Cellular Signatures database. (June 2015) - Won, Shen-Jeu; Wu, Hsing-Chih; Lin, Kuan-Ting; Yu, Cheng-Hao; Chen, Yi-Ting; Wu, Chi-Shiuan; Huang, Chi-Ying F.; Liu, Hsiao-Sheng; Lin, Chun-Nan; Su, Chun-Li
Highlights: Identify possible molecular actions of phytochemicals using L1000 and LINCS database. L1000 is to quantify mRNA expressions of 1000 selected landmark genes per sample. LINCS database stores more than 1.3 million L1000 profiling results. A novel natural lignan justicidin A was revealed to act as autophagy inducer. Justicidin A indeed induced autophagy and enhanced chemosensitivity of sorafenib. Abstract: Justicidin A (JA), a novel arylnaphthalide lignan, was previously found to reduce the growth of human hepatocellular carcinoma cells (HCC), Hep 3B cells, in NOD-SCID mice via induction of apoptosis. Here, using L1000 microarray profiling obtained from JA-treated HCC cells, the z-score signatures of JA exhibited positive connectivity to known autophagy inducers among 3122 compounds from the Library of Integrated Network-based Cellular Signatures database. JA-induced autophagy in HCC Hep 3B cells was confirmed by formation of acidic vesicular organelles and an increase in the expression of LC3-II and LAMP2a. JA-induced autophagic flux was demonstrated by accumulation of LC3-II and LAMP2a, as well as a decrease in colocalization of LC3 and LAMP2a puncta in the presence of autophagy inhibitor bafilomycin A1. Administration of bafilomycin A1 also demonstrated that JA-induced autophagy suppressed apoptosis. Activation of Ras/MEK/ERK pathway was observed. Following administration of apoptosis inhibitor zVAD, it was found that JA-induced apoptosis did not affect JA-induced autophagy. It is noteworthy that addition of JA promoted chemosensitivity of sorafenib, the only FDA-approved targeted therapy for advanced HCC. The results demonstrate the effectiveness of this novel strategy for rapid discovery of molecular actions of small molecules and suggest the applications of JA in HCC treatment.